Burpee Interval Training Is Associated With a More Favorable Affective Valence and Psychological Response Than Traditional High Intensity Exercise. Issue 3 (June 2022) - Mayr Ojeda, Erika; Castro, Flávio Antônio de Souza; Reich, Micaela; Astorino, Todd A.; Benítez-Flores, Stefano
Acute psychological responses to physical activity may help explain long-term adherence to it. Thus, we compared acute psychological responses to different exercise protocols with identical durations. Eighteen moderately active young adults [ M age = 23, SD = 3 years; M VO2max (maximum oxygen consumption) = 42.8, SD = 4.3 mL·kg −1 ·min −1 ; M BMI (body mass index) = 24, SD = 2 kg·m −2 ] completed three low-volume exercise sessions in a crossover research design: (a) sprint interval training (SIT), (b) burpee interval training (BIT) requiring 10 × 5 second efforts with 35 seconds of passive recovery, and (c) a single bout of vigorous intensity continuous training (VICT) requiring 6 minutes and 5 seconds of running at ∼85% of peak heart rate (HRpeak ). We assessed participants' ratings of perceived exertion (RPE), affective valence, enjoyment, intention, preference, and self-reported recovery and wellness before, during, and after each session. BIT was associated with significantly greater enjoyment, preference, and exercise intention (at 5 × week) than VICT ( p ≤ .05). SIT elicited greater RPE ( M = 5.38, SD = 2.00) than both BIT ( M = 2.88, SD = 1.23) and VICT ( M = 3.55, SD = 1.38) ( p ≤ .05), and we observed a higher increase in RPE over time with SIT versus BIT ( p = .019). For affective valence, SIT ( M = 0.55, SD = 2.12) elicited a more aversive response than both BIT ( M = 2.55, SD = 1.09) and VICT ( M = 1.94, SD = 1.51) ( p ≤ .05), and there was a higher increase in this aversive response to SIT over time ( p < .05). Forty-eight-hour postexercise session muscle soreness was significantly lower with VICT than with BIT ( p = .03). Overall, BIT was associated with more positive psychological responses than SIT and VICT.